Environmental Protection Funds As A Component Of National Financial And Environmental Security: Administrative And Legal Regulation - Liudmyla Сhupryna; Nataliia Zadyraka; Andrii Koshlia; Mykola Chabanenko; Lemekha Rostislav (Jurnal Cita Hukum, 2022)
The purpose of the research. The scientific article is devoted to the coverage of the environmental protection funds as a component of national financial and environmental security. Main  content. It is substantiated that achieving the effectiveness of regulatory policy in the field of environmental protection requires the state to intensify the forms of its implementation, one of which is the activities of extra-budgetary trust funds. During the analysis of economic and sectoral extra-budgetary funds, the unification of legal regulation of the procedure for allocating funds provided to environmental funds was identified as a necessary measure, which will allow detailed regulation of such rules and establish a mechanism for liability for violations. Methodology:  Consideration of materials and methods based on the analysis of documentary materials for the environmental protection funds as a component of national financial and environmental security. Conclusions. The expediency of systematizing the legislation regulating extra-budgetary funds is argued for the purpose of further elaboration and adoption of the Law of Ukraine “On Public Funds”.Keywords: administrative service, environmental tax, government service, municipal service, electronic service, public service.